THU0206 Add-on short-course tocilizumab accelerates dose tapering of glucocorticoids in rheumatoid arthritis: results from a chinese prospective cohort study. (12th June 2018) - Wang, J.-W.; Mo, Y.-Q.; Wang, X.-Y.; Chen, L.-F.; Ma, J.-D.; Lin, J.-Z.; Zheng, D.-H.; Dai, L.
Abstract : Background: In real-world clinical practice, self-paid and expensive price limit the application of bDMARDs and only a few patients especially in developing countries could afford long-term use. Only 9.1%>11% of Chinese rheumatoid arthritis (RA) patients were treated with bDMARDs with mean course no more than 6 months. Such short course of bDMARDs had always been raised doubt about their efficacy and benefit for rare reported evidence. Objectives: To explore the efficacy of additional short-course of Tocilizumab (TCZ) combined with csDMARDs in real-world RA management. Methods: Consecutive patients with active RA (DAS28-ESR>2.6) who had completed 6 month follow-up were retrospectively recruited from a prospective RA cohort (n=582). All patients were treated according to the treat-to-target strategy and patient's willingness especially biologics use. RA patients who finished at least 3 infusions of TCZ (8 mg/Kg/4 weeks) were included as add-on TCZ group, and matched RA patients without any bDMARDs by age, sex and disease activity at baseline with the ratio of 1:1 were included as csDMARDs group. Clinical data were collected according to the 2017 EULAR recommendation at baseline and regular visits at week 4, 12 and 24. Results: (1) The baseline characteristics of 101 paired RA patients showed no significant difference except for lower csDMARDs-naïve percentage between two groups (table 1). (2) During 24 week follow up, there were significantly higher percentage of patients in add-on TCZ group achieving therapeutic target (DAS28-ESR<3.2, at Week 4: 59% vs. 39%, p=0.005; at Week 12: 71% vs. 52%, p=0.006, figure 1) or remission (DAS28-ESR<2.6, at Week 4: 46% vs. 16%, p<0.001; at Week 12: 53% vs. 28%, p<0.001) than those in csDMARDs group. Furthermore, there were significantly higher percentage of patients in add-on TCZ group achieving deep remission (DAS28-ESR≤1.98, at Week 4: 16% vs. 5%, p=0.015; at Week 12: 28% vs. 9%, p=0.001; at Week 24: 20% vs. 9%, p=0.046). (3) There were 76% RA patients in add-on TCZ group with glucocorticoids (GC) therapy which is significantly lower than that in csDMARDs group (92%, p=0.002). Among patients with GC therapy, the GC dosage per day was tapered more rapidly at each visit and the cumulative dose at week 24 was significantly lower in add-on TCZ group than that in csDMARDs group (826±616 vs. 1128±519 mg, p<0.001). Conclusions: Add-on short-course TCZ may be an alternative induction strategy for RA patients in developing countries which can quickly achieve target and accelerate dose tapering of GC. Acknowledgements: This work was supported by National Natural Science Foundation of China (grant no. 81471597, 81671612 and 8160147) and Guangdong Natural Science Foundation (grant no. 2016A030313307 and 2017A030313576). Disclosure of Interest: None declared